Ultrasound guided interscalene brachial plexus block via lower approach for upper limb surgeries - Garaniya, Roopal R.; Shah, Sheetal; Prajapati, Noopur (International Journal of Advances in Medicine, 2018)
Background: Brachial plexus block via interscalene approach is an excellent option for upper limb surgeries, but due to sparing of ulnar nerve (lower trunk, C8-T1) and its’ complications, it is not so popular. To overcome this problem, interscalene block via lower approach has been tried which has more advantage in view of ulnar nerve blockage and also less complications. In addition, ultrasound provides reliability, ease, rapidity and also patient comfort during block procedure. This prospective study was performed to evaluate the anaesthetic effect of lower approach interscalene block with the help of ultrasound and peripheral nerve stimulator. Methods: Ultrasound guided interscalene brachial plexus block via lower approach was given in randomly selected 30 patients, undergoing upper limb orthopaedic surgeries. After localisation of brachial plexus with ultrasound, the nerve roots were confirmed with the help of peripheral nerve stimulator, before injecting drug. At 5 and 15 min after block, all patients were assessed for the effect. Postoperatively they were assessed for any complication and also for their satisfaction level by Likert’s scale. Results: In territories of ulnar, radial and musculocutaneous nerve there was 100% effect while in median nerve territory 92.8% motor block was there. There was no need of analgesics during intra operative period in any patient and there were no major complications with this approach. Conclusions: Ultrasound guided interscalene block via lower approach is an excellent alternative for upper limb surgeries over classical approach in view of ulnar nerve blockage without any major complication.